Evolution challenges : integrating research and practice in teaching and learning about evolution - Rosengren, Karl Sven. (Oxford : Oxford University Press, 2012)
This book goes beyond the science versus religion dispute to ask why evolution is so often rejected as a legitimate scientific fact, focusing on a wide range of cognitive, socio-cultural, and motivational factors that make concepts such as evolution difficult to grasp.
Includes bibliographical references and indexes.
Description based on print version record.
Keywords: Evolution (Biology) -- Study and teaching; Evolution (Biology) -- Social aspects; Education -- Research; Effective teaching; Cognitive learning; Educational psychology